2022
DOI: 10.3389/fimmu.2022.824459
|View full text |Cite
|
Sign up to set email alerts
|

Fast Maturation of Splenic Dendritic Cells Upon TBI Is Associated With FLT3/FLT3L Signaling

Abstract: The consequences of systemic inflammation are a significant burden after traumatic brain injury (TBI), with almost all organs affected. This response consists of inflammation and concurrent immunosuppression after injury. One of the main immune regulatory organs, the spleen, is highly interactive with the brain. Along this brain–spleen axis, both nerve fibers as well as brain-derived circulating mediators have been shown to interact directly with splenic immune cells. One of the most significant comorbidities … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 123 publications
(147 reference statements)
0
2
0
Order By: Relevance
“…Initially, there is a pro-inflammatory phase where the spleen contracts within 1-4 days, coinciding with an elevated release of lymphocytes and monocytes into the bloodstream [11,61,63,64]. A similar biphasic spleen cycle was shown in humans post-stroke [62] and post-TBI [77]. Spleen responses have been demonstrated to hinder stroke recovery [13,39,40].…”
Section: Discussionmentioning
confidence: 82%
“…Initially, there is a pro-inflammatory phase where the spleen contracts within 1-4 days, coinciding with an elevated release of lymphocytes and monocytes into the bloodstream [11,61,63,64]. A similar biphasic spleen cycle was shown in humans post-stroke [62] and post-TBI [77]. Spleen responses have been demonstrated to hinder stroke recovery [13,39,40].…”
Section: Discussionmentioning
confidence: 82%
“…In particular, DCs are essential to provide immunity against lung infections, including viral and bacterial pneumonia [ 28 , 53 57 ]. A recent study reported rapid maturation of DCs, possibly due to increased phosphorylation of Flt3 receptor, metabolic activity, protein synthesis, lysosomal activity, and inflammatory properties within few hours of TBI [ 58 ]. On the other hand, data from this current study document that TBI directly affects the pool and composition of DCs in almost all lymphoid and non-lymphoid organs, including lungs at early and sub-chronic phases of TBI.…”
Section: Discussionmentioning
confidence: 99%